[BILL OF RIGHTS AS MARKETING TOOL] (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Article revealing the ulterior motives behind Philip Morris' promotion of the Bill of Rights. Claims Philip Morris is using the Bill of Rights as a marketing tool to emphasize the freedom and rights of all American citizens, including those of smokers. Explains that recent health reports about the harms of tobacco smoke and subsequent anti-smoking legislation have pushed the tobacco industry to focus on smokers' rights.